Long-term outcome of interstitial lung disease in patients with primary Sjögren’s syndrome: a retrospective observational study - Jung Hee Koh; Youngjae Park; Jennifer Lee; Howook Jeon; Su-Jin Moon; Yong Hyun Kim; Jun-Ki Min; Sung-Hwan Park; Seung-Ki Kwok (The Korean Journal of Internal Medicine)
Background/Aims Interstitial lung disease (ILD) is a potentially serious but underdiagnosed manifestation of primary Sjögren’s syndrome (pSS). This observational study investigated the prevalence and clinical course of ILD in pSS, together with prognostic factors. Methods A multicenter, retrospective longitudinal study was performed using findings from baseline and follow-up pulmonary function tests and chest computed tomography. Predisposing factors for the development of ILD and acute exacerbation (AE) were identified using a logistic regression model. The risk factors for a significant decline of pulmonary function were determined by the Cox proportional hazard model. Results A total of 1,306 patients with pSS were included in this study (female, 98%; mean age, 54 years). Among them, 79 patients with pSS were comorbid with ILD. ILD was more frequently found in male, older patients. Nonspecific interstitial pneumonia was the most prevalent imaging pattern in pSS-ILD (51%), followed by usual interstitial pneumonia (22%). At diagnosis with pSS-ILD, 54% of patients had restrictive pulmonary function, and 41% of patients initiated pharmacological treatment. During the median 4-year follow-up period, AE, a significant decline in pulmonary function, and death occurred in 19%, 29%, and 9% of patients with pSS-ILD, respectively. The neutrophil-to-lymphocyte ratio (NLR) increased 3 months prior to AE, and it was associated with AE. Older age at pSS-ILD diagnosis was a prognostic factor for a significant decline in pulmonary function. Conclusions ILD accounted for 6% of the comorbidity of pSS. AE was associated with a significant decline in pulmonary function, and the NLR may predict AE.